Roland Barthes’ Semiotic Analysis of Feature Text Written by the Students in Language and Literature Education Study Program - Asdah, Atikah Nurul; Apyunita, Devi (LITERA : Jurnal Bahasa Dan Sastra, 2025)
This study aims to investigate the structure of meaning and the embedded cultural values in nature-themed feature texts composed by students of the Indonesian Language and Literature Education program. Employing a qualitative descriptive approach, the study adopts a semiotic text analysis design. Data were collected through documentation of the feature texts and semi-structured interviews. The analysis was guided by five semiotic codes: hermeneutic, semic, symbolic, proairetic, and cultural. The findings revealed that the students’ feature texts consistently incorporate all five semiotic codes, each contributing to the enrichment of narrative structure and depth of textual meaning. The hermeneutic code generates curiosity and suspense; the semic code conveys connotative meanings; the symbolic code represents cultural and spiritual symbolism; the proairetic code structures the narrative flow; and the cultural code reflects local cultural values. Moreover, the texts exhibit significant values such as aesthetic awareness, ecological consciousness, cultural preservation, and spiritual reflection. This study concluded that students’ feature texts function as a medium of personal and cultural expression, while simultaneously serving as a tool for critical literacy. These texts support transformative learning and foster cultural identity reinforcement within educational contexts.